Economic security for a better world - ILO Socio-Economic Security Programme (Geneva International Labor Office, 2004)
Drawing primarily on a special Global Database of national statistical indicators, coupled with a set of People's Security Surveys, covering over 48,000 households in 15 countries, and a set of Enterprise Labour Flexibility and Security Surveys, covering over 10,000 firms in 12 countries, provide a picture of the emerging patterns of economic security across the world.
Part I. 1 Conceptualizing people's security -- 2 The liberalization context of insecurity -- Part II. Monitoring socio-economic security -- 3 Income security: The deepening divide -- 4 Monitoring income security -- 5 Labour market security -- 6 Employment security -- 7 Work security -- 8 Skills security -- 9 Job security -- 10 Voice representation security -- 11 The Economic Security Index -- Part III. 12 Attitudes to economic justice and security -- 13 Emerging forms of voice representation security -- 14 Seeking income security --
Includes bibliographical references (p. 429-447).
Keywords: Economic conditions; LIVING CONDITIONS; WORKING CONDITIONS; ECONOMIC CONDITIONS; INCOME DISTRIBUTION; SOCIAL SECURITY; EMPLOYMENT SECURITY; DEVELOPING COUNTRIES; DEVELOPED COUNTRIES